On leaderless consensus of fractional-order nonlinear multi-agent systems via event-triggered control - Wang, Fei; Yang, Yongqing (Nonlinear Analysis: Modelling and Control, 2019)
The consensus problem of fractional-order multi-agent systems is investigated by eventtriggered control in this paper. Based on the graph theory and the Lyapunov functional approach, the conditions for guaranteeing the consensus are derived. Then, according to some basic theories of fractional-order differential equation and some properties of Mittag–Leffler function, the Zeno behavior could be excluded. Finally, a simulation example is given to check the effectiveness of the theoretical result.